In Situ Filling of the Oxygen Vacancies with Dual Heteroatoms in Co3O4 for Efficient Overall Water Splitting - Wei Duan; Shixing Han; Zhonghai Fang; Zhaohui Xiao; Shiwei Lin (Molecules, 2023)
Electrocatalytic water splitting is a crucial area in sustainable energy development, and the development of highly efficient bifunctional catalysts that exhibit activity toward both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) is of paramount importance. Co3O4 is a promising candidate catalyst, owing to the variable valence of Co, which can be exploited to enhance the bifunctional catalytic activity of HER and OER through rational adjustments of the electronic structure of Co atoms. In this study, we employed a plasma-etching strategy in combination with an in situ filling of heteroatoms to etch the surface of Co3O4, creating abundant oxygen vacancies, while simultaneously filling them with nitrogen and sulfur heteroatoms. The resulting N/S-VO-Co3O4 exhibited favorable bifunctional activity for alkaline electrocatalytic water splitting, with significantly enhanced HER and OER catalytic activity compared to pristine Co3O4. In an alkaline overall water-splitting simulated electrolytic cell, N/S-VO-Co3O4 || N/S-VO-Co3O4 showed excellent overall water splitting catalytic activity, comparable to noble metal benchmark catalysts Pt/C || IrO2, and demonstrated superior long-term catalytic stability. Additionally, the combination of in situ Raman spectroscopy with other ex situ characterizations provided further insight into the reasons behind the enhanced catalyst performance achieved through the in situ incorporation of N and S heteroatoms. This study presents a facile strategy for fabricating highly efficient cobalt-based spinel electrocatalysts incorporated with double heteroatoms for alkaline electrocatalytic monolithic water splitting.